Assessing the Suitability of a Wastewater Reuse System for Non-potable Applications - Paul Wafula Bwire (Uganda Christian University, 2025)
This project addresses the problem of the high cost of using potable water to carry out low quality tasks such as flushing in toilets and urinals by offering a sustainable, yet environmentally friendly way of harnessing treated wastewater effluent for these non-potable applications. In this research, the quality of raw effluent from the UCU activated sludge treatment plant was assessed and determined. This information was then input into design calculations to design an effluent polishing system and a non-potable water distribution system. Uganda Christian University (UCU) purchases between 6000 to 7000 m3 of potable water from National Water and Sewerage Corporation (NWSC) on a monthly basis. This water is used to ensure smooth running university activities such as cleaning, cooking, drinking, and waste management. Studies show that about 20-40% of domestic water demand is consumed in toilet flushing and 50-70% of commercial water demand.
Under Graduate Research